Outcomes of proximal versus total gastrectomy for proximal gastric cancer: A propensity score-matched analysis of a western center experience - UPRAK, TEVFİK KIVILCIM; ERGENÇ, MUHAMMER; AKMERCAN, AHMET; YEGEN, ŞEVKET CUMHUR (My University, 2023)
Purpose: In this western study, we aimed to compare perioperative outcomes, postoperative complications, and overall survival in patients who underwent total gastrectomy (TG) or proximal gastrectomy (PG) for proximal gastric cancer (GC). Methods: Patients who underwent GC surgery at Marmara University Hospital between January 2014 and December 2021 were evaluated retrospectively. Propensity score matching (PSM) was performed to balance the baseline characteristics of patients undergoing PG and TG. Data on patients’ demographics, clinicopathological features of tumors, complications, and survival rates were analyzed. Perioperative outcomes and overall survival of the patients were compared between PG and TG groups. Results: A total of 212 patients were included in this study, with 53 patients in the PG and 159 in the TG group. After 1:1 matching according to PSM, 46 patients in the PG group were matched to 46 in the TG group. After PSM, there were no differences in clinicopathological outcomes except retrieved lymph nodes. In terms of short-term outcomes, overall perioperative morbidity (Clavien Dindo ≥ 3a) was significantly higher in the PG group (p = 0.01). However, there was no significant difference when the complications were considered separately. In the long-term follow-up, reflux esophagitis was associated with the PG group (p=0.04). In multivariate analysis, positive surgical margin and lymphovascular invasion were significant factors related to overall survival. Overall, 5-year survival was 55% in matched patients. The difference in survival was not statistically significant (57 vs. 69 months, p = 0.3) between the two groups. Conclusions: Proximal gastrectomy is applicable to patients up to stage 3 disease, with no difference in overall survival, with caution in early complications and reflux esophagitis. Among all demographic and oncological factors, lymphovascular invasion and resection margin were significantly associated with worse survival.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; GASTROENTEROLOJİ VE HEPATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; GASTROENTEROLOGY & HEPATOLOGY; Cerrahi; Gastroenteroloji; Surgery; Gastroenterology; Carcinoma stomach; Gastrectomy; Proximal gastrectomy; Proximal gastric cancer; Total gastrectomy; Carcinoma stomach; Gastrectomy; Proximal gastrectomy; Proximal gastric cancer; Total gastrectomy